Aplikasi Inventarisasi Aset Berbasis Web Dengan Metode Waterfall - Pinem, Sanjaya; Pakpahan, Victor Maruli (Teknik Informatika Universitas Pamulang, 2020)
Asset inventory management in SMP Negeri 3 Tanah Jawa, Simalungun Regency, still uses the Microsoft Excel application and manual recording. This causes the data collection to be complicated or difficult to manage because the recording is only done on paper and stored in a file cabinet so it is very difficult to see and report data that has been long. As a result, reporting of goods entering and leaving goods occurs an error and is late. This problem was overcome by designing web-based applications. Applications are built using the waterfall method, starting with data collection through observation and interviews, analyzing system requirements to be evaluated based on system testing. Through this application, the process of recording and reporting asset variation can be accessed easily and in an organized manner.